EVOLUSI GERAKAN HTI DAN ANCAMAN TERHADAP GENERASI MUDA ISLAM - Taqwa, Libasut (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2015)
After the fall of Soeharto’s regime, Indonesia has experienced changes in many aspects of such social life as politics, economy, and education. Soon, transnational-religious party has emerged. Hizbut-Tahrir Indo-nesia (HTI) has started its new agenda and mission, namely enforcing the Islamic Caliphate and Shari'a and changing the Indonesia’s Consti-tution with the new constitution they propose. This article a conceptual writing which deals with three objectives, are: analyzing the extent of the movement, the evolution of transnational Islamic religion, and how HTI has successfully gained sympathy and support from the Indone-sian young Muslims who subsequently become it loyal followers with strong militancy. The writer concludes that HTI along with its propaganda has, in fact, threatened national concept of Indonesia’s constitution. Therefore, it is important to protect the young generation from such ideological propaganda as discussion, organization, mass media, and other means employed by HTI in order to influence them.